Some remarks about the annual sub-nitrophilous vegetation of Thero-Brometalia in Umbria (central Italy) - Gigante, Daniela; Venanzoni, Roberto (Lazaroa, 2007)
Some data concerning the annual sub-nitrophilous vegetation widespread in western and south-western Umbria are presented. From a bioclimatic point of view, the analysed areas can be referred partly to the temperate and partly to the Mediterranean macrobioclimate, whereas from a geological point of view they are very heterogeneous (as shown later in detail). The dominant species in the different plant communities studied are Trifolium stellatum, T. resupinatum, T. nigrescens, Melilotus neapolitanus and Aegilops neglecta. They are common in mildly disturbed environments: for instance on pathway edges, fields edges or olive groves. A phytosociological setting is here proposed for these plant communities, inside the Stellarietea mediae class, the Thero-Brometalia order and the Taeniathero-Aegilopion geniculatae and Echio-Galactition tomentosae alliances. New data about their syndynamical relations, distribution, ecological characterisation and floristic composition inside the study area are reported.